An intensive non-invasive protocol combining non-surgical spinal decompression and supportive physiotherapeutic modalities in the treatment of double-level disc herniation at L4-L5 and L5-S1: A case report - Vincenzo Di Modica; Giuseppe J. Sciarrone (Trauma Case Reports)
Background: Given the low prevalence of multi-level disc herniations, robust clinical evidence for their management remains limited, particularly concerning non-invasive treatments, where data is nearly non-existent. However, an intensive therapeutic regimen centered on non-surgical spinal decompression (NSSD)11 NSSD: Non-Surgical Spinal Decompression; AP: Anteroposterior; LDH: Lumbar Disc Herniation; FNTT: Femoral Nerve Tension Test; SLRT: Straight Leg Raising Test; MRC: Muscle Research Council; HI: Herniation Index; HL: Herniation Length; HW: Herniation Width; TCL: Total Canal Length; TCW: Total Canal Width., augmented with supportive physiotherapy modalities, demonstrates promise in the non-invasive management of significant lumbar disc herniations, even when affecting multiple spinal levels concurrently. Case report: A 46-year-old female patient presented with double-level disc herniations at the L4-L5 and L5-S1 segments. Following the failure of two conventional physiotherapy regimens, surgical intervention was advised as the sole treatment option. The patient, however, declined invasive surgery and opted for an intensive six-month program predominantly based on NSSD therapy. Magnetic resonance imaging scans taken after the initial onset of symptoms, prior to and two months after initiating the program, and one month following its completion, revealed significant improvements across all monitored parameters, including canal anteroposterior (AP)1 length and area, disc AP length and area, and herniation index. These structural changes indicated an almost complete restoration of the canal surface and substantial reduction of herniation at both affected levels. Conclusions: Even in patients with significant herniations at two different levels, substantial improvement can be achieved through a non-invasive approach. These findings underscore the effectiveness of an intensive treatment program utilizing NSSD therapy and offer a viable alternative for patients who are unable or unwilling to undergo surgical intervention.